Co-operative Retailing: Interference of Consumerfed in Essential Goods Market in Kerala - T.P.Vijumon (International Journal of Business and Management Invention, 2013)
Retailing is considered as the largest sector both in contribution to GDP and employment among many countries in the world. It plays a predominant position in the economies of all developed countries. It has been one of the fastest growing sectors and contributes more than one-fourth of the GDP of many countries in the world. The sector contributes more than 20 percent employment in the world. Organised retailing is dominant in most of the European countries, USA, Canada, Australia, etc. In India this form of retailing is just started its growth and presently less than ten percent of total retail turn over. Co-operatives as peoples’ organization have engaged in retailing activities in India around 1904 when the Triplicane Co- operative store started functioning in Madras. Then hundreds of co-operatives were staged functioning in the countryand became fullfeged peoples organisation by distributing consumer goods at lowest prices. Many Supermarkets having multi-million turnover are functioning in co-operative sector, like Apna Bazar in New Delhi. In 1964, the 28 State Co-operative Consumers’ Federations were started in India. The Kerala State Co- operative Consumers Federation Ltd is the most prominent among them as it has more than 1232 consumer retail outlets in the state to supply consumer goods and to interfere the essential goods market. Here an attempt is done to describe the role played by them and effectiveness in their activities from customers’ point of view.